menu
bartleby
search
close search
Hit Return to see all results

Let f(x)=3−xf(x)=3-x and g(x)=x3+6g(x)=x3+6, find: (g∘f)(x)

Question

Let f(x)=3−xf(x)=3-x and g(x)=x3+6g(x)=x3+6, find: (g∘f)(x)

check_circleAnswer
Step 1

The given functions are f(x)=3-x ...

(gofx)g ((x))
help_outline

Image Transcriptionclose

(gofx)g ((x))

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Our solutions are written by experts, many with advanced degrees, and available 24/7

See Solution
Tagged in

Math

Calculus

Related Calculus Q&A

Find answers to questions asked by student like you

Show more Q&A add

Sorry about that. What wasn’t helpful?